(untitled) (Global Journal of Management and Business Research, 2011)
Organizations in the region implement the ISO 9000 Quality Management System and obtain the consequent approvals, rewards and certificates, but unfortunately, without the actual and effective implementation on the ground. The purpose of this research study was to assess the impact of the implementation of the ISO Quality Management System upon the performance of participating workers. Qualitative as well as quantitative research was conducted. Data were collected using a quantitative survey administered to 150 participants from either governmental or private and both sectors in the State of Qatar. Findings include the implementation of the ISO 9000 QMS has no impact on the performance of the participating organizations’ workers. This research study also revealed some important points related to the organizations’ workers and their performances under the umbrella of the ISO 9000 Quality Management System, which leads the Researcher to raise some questions to the concerned people in the International Organization for Standardization (ISO).